Climate Smart Agriculture Partnership for Africa: Prospects and Challenges - Mapfumo, Paul; Nyasimi, Mary; Speranza, Chinwe Ifejika; Wamukoya, George; Kinyangi, James (African Centre for Technology Studies, 2017)
There is overwhelming evidence that Africa needs to change its agricultural systems for increased productivity, resilience and competitiveness in ensuring food security, income generation, as well as minimization of negative impacts on environment. Research shows that the current agricultural systems are inadequate in meeting the food security and livelihood needs of the continent’s growing population, estimated to reach 1.9 billion by 2050. The purpose of this chapter, is twofold: a) respond to the critical need to reduce vulnerability of the African agricultural sector to climate change and variability, among other inherent multiple factors undermining the socio-economic development of the majority of nations; and b) address the need to inform Africa’s role in the emerging Global Alliance on Climate Smart Agriculture (CSA). Specifically, the chapter sets out to achieve the following objectives: i) identify the challenges and opportunities for CSA in Africa in the context of transformative pathways for achieving sustainable agricultural development on the continent, ii) propose a technical framework for a functional, responsive and inclusive partnership on CSA in Africa; and iii) develop a guide towards a common vision, objectives, and development outcomes for a climate-smart agricultural development thrust in major regions of Africa. The chapter also serves to support national and regional agricultural and climate change policy development and implementation processes, guide development donors seeking to support Africa’s agricultural transformation, and also equip African climate change negotiators with key messages to support Africa’s unified position on agriculture.